BIOGRAPHICAL (AUTO) MEMORIES OF A NURSE IN THE TEACHING EXERCISE: PERSONAL AND PROFESSIONAL PATH: PERSONAL AND PROFESSIONAL PATH - Amorim, Rita (2024)
This memorial aimed to recall our personal and professional path throughout our existence from the various interactions with family, friends, friends, students, students, teachers, teachers, resulting in the professional woman we are discovering and being discovered, with the loves and pains that make life pulsate, of one of the stages of the career progression process for full professor of the Higher Teaching of the State University of Feira de Santana-UEFS. It has a descriptive character. In the process of elaboration we find the memories of our personal and professional experiences. One moment, as a daughter, granddaughter, niece, sister, cousin, friend, colleague and another as a student, nurse and teacher, because we made the choice of writing (auto) biographical. Thus, we present some of the various possibilities of interactions throughout the course of our life, notably family and professional. We narrate about our years of institutionalized studies, from literacy to postgraduate studies, acting as a nurse in a public health institution and in another public institution of higher education and other activities in the professional field. Finally, we present our concerns for the future.